El método en dos investigaciones urbanas: Estación Plaza de Bolívar e Imaginarios y representaciones en el transporte público de pasajeros (2008)
The first urban investigations were carried out starting from the semiótica in the ways and they looked for to define those elements or significant that transmit the city meaning. Then, he/she incorporated the category desire that allowed to look at the sense of the city beyond their formal meaning, this is the significant practice. Inside this investigation line, the observation that here is presented, it passed of a static look in the work “Station Square of Bolívar”, to a city in movement in the work “Imaginary and representations in the public transportation of passengers.” Among these two investigations a methodological change induced by the movement and the necessity of looking for fragmentary scenes along journeys took place. The objective of this article is to confront those methodologies, the hypotheses and the theoretical references of both investigations.